2024
DOI: 10.1042/bst20230596
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical approaches to assess the impact of post-translational modifications on pathogenic tau conformations using recombinant protein

Mohammed M. Alhadidy,
Nicholas M. Kanaan

Abstract: Tau protein is associated with many neurodegenerative disorders known as tauopathies. Aggregates of tau are thought of as a main contributor to neurodegeneration in these diseases. Increasingly, evidence points to earlier, soluble conformations of abnormally modified monomers and multimeric tau as toxic forms of tau. The biological processes driving tau from physiological species to pathogenic conformations remain poorly understood, but certain avenues are currently under investigation including the functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 201 publications
0
1
0
Order By: Relevance
“…Additionally, we demonstrated that EFhd2 does not affect ARA-induced tau filament formation. Thus, EFhd2 is a tau-associated protein that induces the formation of entangled tau filaments (Alhadidy and Kanaan, 2024). Nonetheless, it is worth mentioning that pathological tau also undergoes diverse molecular changes, including phosphorylation, acetylation, truncation, and other modifications, which could contribute to its aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we demonstrated that EFhd2 does not affect ARA-induced tau filament formation. Thus, EFhd2 is a tau-associated protein that induces the formation of entangled tau filaments (Alhadidy and Kanaan, 2024). Nonetheless, it is worth mentioning that pathological tau also undergoes diverse molecular changes, including phosphorylation, acetylation, truncation, and other modifications, which could contribute to its aggregation.…”
Section: Discussionmentioning
confidence: 99%